Active-metal template clipping synthesis of novel [2]rotaxanes - Anghel, Cătălin C.; Cucuiet, Teodor A.; Hădade, Niculina D.; Grosu, Ion (Beilstein Journal of Organic Chemistry, 2023)
Mechanically interlocked molecules (MIMs) have been important synthetic targets in supramolecular chemistry due to their beautiful structures and intriguing properties. We present herein a new synthetic strategy to access [2]rotaxanes, namely active-metal template clipping. We discuss the design of the target [2]rotaxanes, synthesis and characterization of the axle, macrocycle precursors and macrocycles as well as preparation of the final [2]rotaxanes by active template copper(I)-catalyzed alkyne–azide cycloaddition (CuAAC) as key step of the synthesis. HRMS and NMR experiments have been performed to confirm the formation of the interlocked structures.
Keywords: active-metal template; clipping; copper(I)-catalyzed alkyne–azide cycloaddition; mechanically interlocked structures; [2]rotaxanes